Spectroscopic Techniques using Synchrotron Radiation and Free-Electron and Conventional Lasers - Tadjeddine, A (Journal of synchrotron radiation, 1998)
Considerable progress in the investigation of the electronic and vibrational properties of atoms, molecules, materials, surfaces and interfaces has been achieved by combining different photon sources of complementary characteristics. In this paper some experimental results obtained recently at LURE by using two synchronized sources, such as the IR free-electron laser (FEL) CLIO, the VUV storage ring FEL, synchrotron radiation and table lasers, are presented. Using CLIO synchronized with a YAG laser allows the investigation of the vibrational properties of adsorbed species by the non-linear optical technique of visible-IR sum (difference) frequency generation, as shown for the adsorption of hydrogen on platinum in the electrochemical environment. The second result reported here relates to the study of the intersubband stimulated emission in GaAs/GaAlAs quantum wells by pump-probe experiments using the two-colour configuration of CLIO. The combination of a mode-locked Ar(+) laser and synchrotron radiation has been used for investigations in a pump-probe arrangement of the ionization of Xe atoms via the resonant state Xe* 5p(5)5d [3/2](1). The final example is a time-resolved core-level spectroscopy study of photoexcited Si(111) 2 x 1 surfaces by using a combination of the naturally synchronized UV storage ring laser and synchrotron radiation